Human Resource Management in the Era of Caliph ʿUmaribnKhaṭṭāb (R.A.) [13AH-23AH] - Kiran, Faiza; Nadeem, Dr. Abid (Al-Irfan, 2022)
Human Resource Management is basically a system that influences the workforce. It consists of the acquisition, development, motivation, and maintenance of the available human resource in an organization. Islam integrates spiritual and material progress. It urges its followers to perform their duties at their best. Human resources are considered as the main capital in thedevelopment of a company. But Islamic teachings command that employees are not just a servant, they are valuable assets. Islamic teachings provide the knowledge and understanding of all principles related to recruitment and selection, performance appraisal, training and development, and reward etc. These all have been applied in the Islamic history, it was noticed in the Era of Rāshidūn Caliphate especially in the tenure of the second caliph ʿUmaribnKhaṭṭāb(r.a). He set an exemplary management of Human Resources in the best possible way. A brief introduction to the various cadres and departments during his reign related to Human Resource Management is given below.